Parental Perspectives on Distance Learning Challenges for Arabic Language Instruction in Kuwait's Fifth Grade - Al-wattar, Nouri Y. (Forum for Linguistic Studies, 2025)
The COVID-19 pandemic prompted an abrupt shift to distance education in Kuwait, raising urgent concerns about the continuity and quality of Arabic language instruction—especially for younger learners. This study aims to: (1) identify the key challenges parents encountered while supporting Arabic learning for fifth-grade students, (2) assess the extent of parental involvement in online learning, and (3) evaluate parental satisfaction with this experience. These objectives are particularly relevant in the context of Arabic, a language that depends heavily on interactive and immersive instruction, where remote learning presents distinct pedagogical challenges. A descriptive relational quantitative design was employed. Data were collected through a rigorously developed structured questionnaire, completed by 554 parents across six educational districts in Kuwait. The tool underwent expert review and pilot testing, and demonstrated high internal reliability (α = 0.871 for challenges, 0.807 for involvement, 0.723 for satisfaction; overall α = 0.889). Findings revealed that parents encountered major challenges, particularly the lack of interactive digital tools and real-time communication with teachers—barriers that directly hindered effective Arabic instruction. Many parents actively compensated for these limitations by increasing their instructional support at home, indicating high involvement. However, levels of satisfaction were mixed. ANOVA results showed statistically significant differences by gender and educational level, with female and more educated parents reporting greater challenges, while no significant differences were found based on parental age. This study contributes to limited literature on Arabic distance learning by offering validated, demographically sensitive metrics of parental experience. It presents evidence-based recommendations to enhance digital pedagogy and build resilient, culturally responsive distance-learning frameworks in Arabic-speaking contexts.